Implementation of E-learning in the organizations of secondary education - Smirnova, M.A.; Spirina, Ye.А.; Riger, E. (Ye.A.Buketov Karaganda State University Publishing house, 2015)
In article questions of realization of electronic training in the organizations of secondary education of various countries are considered. In world practice electronic training became an integral part of modern education. Authors showed the purposes of electronic training in schools of Kazakhstan. In detail features of implementation of the Kazakhstan project of introduction of system of electronic training in the organizations of secondary education reveal. Now on the basis of updating of structure and the maintenance of system of electronic training at comprehensive schools hold events for granting opportunities of information and telecommunication technologies for educational process.
Орта білім беру мекемелерінде электронды оқытуды жүзеге асыру
Реализация электронного обучения в организациях среднего образования
Keywords: E-learning; secondary education; school students; state programs; the format of training and teaching; educational services and resources; digital educational resource